Optional permissions of the judge in the judicial procedure ecclesiastical penalties - MARCZYK, SYLWIA (Prawo Kanoniczne, 2017)
The issue of discretionary power of the judge is closely connected with the theory of law and using it in practice, although this relationship is not entirely clear. The law theory focuses on legal standards, on the context in which the law does and should affected, it refers to the broad rules, because the rule of law makes a particular pattern of behavior. On the other hand, we have to deal with the statements in these rule of law, which indicate one the possibility of a judge in making a specific activity, in particular the use of available legal norm. The legislature in the Code of Canon Law of 1983. In some cases, gives expression to the discretionary power of the judge. It must be held that this power is a sphere of activity in which the authority may act according to their beliefs settle within the so-called. discretion. In most cases, the freedom in imposing penalties is governed by legislation, although the legislature also gives the judge the power margin and leaves him complete freedom when fixing, tightening and not to impose criminal sanctions. In each of these cases, the judge must behave in accordance with their conscience and prudence, taking into account the principle of fairness, but also to national circumstances. The legislator dipped by giving so much autonomy in action a person judge shows its important role and places it very high in the hierarchy of government entities.